Why are bivalves not detoxified? - Leal, Joana F. (2024)
Paralytic (PSP), diarrheic (DSP), and amnesic shellfish poisonings are among the most prominent foodborne diseases threatening the food security. Because of the absence of legal methods capable of eliminating these biotoxins, the option is to rely on natural detoxification, compromising the availability of protein-based food and imposing severe socioeconomic impacts. In vivo detoxification methodologies have focused on the use of adsorbents (mainly applied to PSP), some of which are combined with nontoxic algae. Alternative methodologies for DSP have emerged, but they are based on absorption inhibition, which may be unfeasible in real situations. It is thus imperative to optimize existing proposals or develop novel, safe, and cost-effective methods so that the solution is seen as an attractive financial investment.